Right-sided hemiagenesis of the thyroid lobe and isthmus: A case report - Tiwari, Prabhat Kumar; Baxi, M; Baxi, J; Koirala, D (Indian Journal of Radiology and Imaging, 2008)
Unilateral or bilateral hypoplasia or agenesis of one or both thyroid lobes, with or without isthmic agenesis, is a rare developmental anomaly. Hemiagenesis of the left lobe is far commoner than of the right. Clinically, these patients may be euthyroid, hyperthyroid, or hypothyroid. Ultrasonography is usually able to diagnose this condition easily, as we demonstrate in this case report of a 37-year-old lady with an incidentally detected thyroid nodule who was found to have hemiagenesis of the right lobe and isthmus.
Keywords: Congenital anomalies; hemiagenesis; thyroid